PEMANFAATAN SARI LIDAH BUAYA (Aloe vera (L.) Burm.f.) DALAM SEDIAAN HARD CANDY - M. Arya Wiguna; Minda Sari Lubis; Gabena Indrayani Dalimunhe; Rafita Yuliarti (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2023)
One of the medicinal plants that have medicinal properties is aloe vera. The development of the use of aloe vera as a food and beverage ingredient is related to the chemical composition of aloe vera which is very good for body health. One of the utilization efforts is to extract or take the juice and process it into hard candy. Hard candy (candy) is a form of processed food from heating a mixture of sugar and fruit juice or food additives to give flavor. The purpose of this study was to formulate hard candy with aloe vera juice as the main ingredient by varying the concentration of aloe vera juice in order to get a good formula in terms of taste and physical evaluation of hard candy.is Hard candy made using the oven pan. The research method used is experimental research. This study used aloe vera juice as a sample, and it was formulated into a hard candy preparation and evaluated including organoleptic tests, hardness tests, soluble time tests, tests, ash content tests, water content tests, pH tests and tests of preference level ( hedonic test) by respondents and then the results are presented descriptively. The results showed that aloe vera juice was formulated into hard candy preparations with a concentration variation of 2.5%; 5%; 10; provide an attractive shape, taste and hardness are quite good, have a pH of 5-6 and meet the requirements of water content with a coefficient of variation of 0.91%; 0.87%; and 0.89% ash content 0.99%; 0.99% and 0.99%. The results of the preference level test show that formula 1 is the best formula that is widely preferred with variations in the content of aloe vera juice. Variations in aloe vera juice content have an influence on the level of liking.